Asuhan Keperawatan Pada Sistem Pencernaan Tn. H dengan Post Op Herniotomy dibangsal Cempaka RSUD Pandan Arang di Boyolali - Santoso, Wahyu; , Agus Sudaryanto, S.Kep., Ns., M.Kes (2013)
Background: Hernia is a bump on skin which initially looks small and it is getting bigger and bigger. It usually appears on thigh fold and it doesn't show any pain in common case. However, the pain is usually appear on epigastrium area or paraumbilika and the it is visceral pain. Objective: this research is to find out the analysis, diagnosis, planning, action and evaluation of nursery care for post op herniotomy patient. Result: after the nursery care given for the patient for 3 x 24 hours, it resulted in the decrease of pain, no sign of infection and the increase of knowledge about the care. Conclusion: patient was diagnosed with discontinuously severe painful b.d on herniotomy tissue, there existed a risk of b.d strange agent injury, and the knowledge of d was low. All happening on Mr. H., had been overcome for three days.